Metagenomic Analysis of the Virome of Mosquito Excreta - Ana L. Ramírez (American Society for Microbiology, 2020)
ABSTRACT Traditional screening for arboviruses in mosquitoes requires a priori knowledge and the utilization of appropriate assays for their detection. Mosquitoes can also provide other valuable information, including unexpected or novel arboviruses, nonarboviral pathogens ingested from hosts they feed on, and their own genetic material. Metagenomic analysis using next-generation sequencing (NGS) is a rapidly advancing technology that allows us to potentially obtain all this information from a mosquito sample without any prior knowledge of virus, host, or vector. Moreover, it has been recently demonstrated that pathogens, including arboviruses and parasites, can be detected in mosquito excreta by molecular methods. In this study, we investigated whether RNA viruses could be detected in mosquito excreta by NGS. Excreta samples were collected from Aedes vigilax and Culex annulirostris experimentally exposed to either Ross River or West Nile viruses and from field mosquitoes collected across Queensland, Australia. Total RNA was extracted from the excreta samples, reverse transcribed to cDNA, and sequenced using the Illumina NextSeq 500 platform. Bioinformatic analyses from the generated reads demonstrate that mosquito excreta provide sufficient RNA for NGS, allowing the assembly of near-full-length viral genomes. We detected Australian Anopheles totivirus, Wuhan insect virus 33, and Hubei odonate virus 5 and identified seven potentially novel viruses closely related to members of the order Picornavirales (2/7) and to previously described, but unclassified, RNA viruses (5/7). Our results suggest that metagenomic analysis of mosquito excreta has great potential for virus discovery and for unbiased arbovirus surveillance in the near future. IMPORTANCE When a mosquito feeds on a host, it ingests not only its blood meal but also an assortment of microorganisms that are present in the blood, thus acting as an environmental sampler. By using specific tests, it is possible to detect arthropod-borne viruses (arboviruses) like dengue and West Nile viruses in mosquito excreta. Here, we explored the use of next-generation sequencing (NGS) for unbiased detection of RNA viruses present in excreta from experimentally infected and field-collected mosquitoes. We have demonstrated that mosquito excreta provide a suitable template for NGS and that it is possible to recover and assemble near-full-length genomes of both arboviruses and insect-borne viruses, including potentially novel ones. These results importantly show the direct practicality of the use of mosquito excreta for NGS, which in the future could be used for virus discovery, environmental virome sampling, and arbovirus surveillance.